Public finance and economic growth: Empirical evidence from developing countries - Matthew O. Odedokun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The study is an empirical test of the effects of different categories of government expenditure, revenue and deficits on economic growth in developing countries. It is based on panel data of annual series over the last three decades for 103 countries, which are further classified into low-income, high-income, mineral exports dependent, and foreign aid dependent groups. Our findings suggest that the effects of the fiscal variables on growth vary across these groups of countries. But broadly, capital expenditure have been detrimental to growth, just as current expenditure on goods and services, while expenditure on wages and salaries is growth-promoting. Also, functional expenditure on general administration and defense have retarded growth while spending on education and, to some extent, transport and communications sector are growth-friendly. Other economic and functional categories of spending generally have mixed effects, which are sometimes statistically insignificant. Non-tax revenue retards growth in only high-income and mineral exporting groups of countries. Taxes on income and profits are growth-retarding, just as taxes on domestic goods and services in all groups, except mineral exporting one. Taxes on international trade are found to be growth-promoting in only the low-income and foreign aid dependent groups of countries. Foreign grants promote growth in only the group of countries that heavily depend on them while fiscal deficits, whether domestically or foreign financed, retard growth.
Keywords: O23; O40; 330; fiscal policy; public finance; economic growth; Öffentliche Finanzwirtschaft; Finanzpolitik; Entwicklungsländer